Building Global South Solidarity: A Constructivist Analysis of Indonesia and Brazilian South-South Diplomacy Prabowo Era - Mohammad Aras Al Rasyid; Ali Maksum (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study analyzes the development of South-South diplomacy between Indonesia and Brazil in the era of President Prabowo Subianto with a constructivist approach. With the main focus on how Global South identity, solidarity narratives, and equality norms shape cooperation between the two countries that are not only driven by economic interests. This study uses a descriptive qualitative approach with the analysis of data documents from presidential speeches, joint statements, official press releases, and policy documents from the governments of Indonesia and Brazil. Documents are coded based on three aspects, namely identity claims, norms, and how issues are framed in trade, food security, education, and technology. These findings show that the Global South discourse is consistently used to affirm equal and solution-oriented partnerships. This framework reinforces mutual expectations, as well as helps diversify partnerships beyond the dominance of Northern states. At the same time, Indonesia and Brazil affirmed their role as middle powers in multilateral forums. Conclusion Global Solidarity South serves as a diplomatic resource that guides cooperation priorities and strengthens the bargaining positions of the two countries.